Comparative analysis of the technical-tactical skills of elite male beach volleyballteams - Papadopoulou, S. D.; Giatsis, G.; Billis, E.; Giannakos, A.; Bakirtzoglou, P. (Sport Science - International Scientific Journal of Kinesiology, 2020)
The aim of the study was to perform a comparative analysis of the technical-tactical skills of elite male beach volleyball teams in the Olympic Games, Athens 2004. In total, thirty-four games (n=34) of the first eight top teams were studied, and 3484 game actions were videotaped. The study was conducted with the use of the `Sportscout` video-analysis program. The efficiency and type of serves, sets and attacks were examined and assessed. The data were analysed and processed with the use of the statistical package SPSS 25.0, and more specifically the Crosstabs command. The non-parametric Chi-square test (x2) was used to identify statistically significant differences. The statistical analysis of results showed significant differences among the teams in the efficiency of ace serves, the type of jump serve, the efficiency of perfect sets and the type of set, as well as in the efficiency of kill attacks (p<0,05).The Brazilian team, who won the Olympic gold medal, was significantly superior to the other teams with regard to all the above skills although they used overhand set to a lower extent (p<0,05). As a conclusion, the technical-tactical skills that result directly in points, such as ace serves and kill attacks seem to play a crucial role in the final outcome of a top-level men`s beach volleyball game, and, therefore should be taken into serious account during training planning.